MACPainP multiaxial classification of pain psychosocial dimension : systematic approach to classify biopsychosocial aspects of pain disorders /: systematic approach to classify biopsychosocial aspects of pain disorders. (2019) - Klinger, Regine; Hasenbring, Monika; Pfingsten, Michael
No abstract available